Identifying areas for improvement in paediatric trauma care in NSW Australia using a clinical, system and human factors peer-review tool. Issue 5 (May 2019) - Curtis, Kate; Kennedy, Belinda; Holland, Andrew J.A.; Tall, Gary; Smith, Holly; Soundappan, Soundappan S.V.; Burns, Brian; Mitchell, Rebecca J.; Wilson, Kellie; Loudfoot, Allan; Dinh, Michael; Lyons, Timothy; et al.
Highlights: Problems in the delivery of clinical care to children suffering traumatic injury were identified in 85% of cases reviewed. Staff action was the most frequently identified causal factor contributing to problems identified. Adverse event rates were lower than those reported in the international literature. Abstract: Background: There is known variability in the quality of care delivered to injured children. Identifying where care improvement can be made is critical. This study aimed to review paediatric trauma cases across the most populous Australian State to identify factors contributing to clinical incidents. Methods: Medical records from three New South Wales Paediatric Trauma Centres were reviewed for children <16 years requiring intensive care; with an injury severity score of ≥9, or who died following injury between July 2015 and September 2016. Records were peer-reviewed by nurse surveyors who identified cases that might not meet the expected standard of care or where the child died following the injury. A multidisciplinary panel conducted the peer-review using a major trauma peer-review tool. Records were reviewed independently, then discussed to establish consensus. Results: A total 535 records were reviewed and 41 cases were peer-reviewed. The median (IQR) age was 7 (2–12) years, the median ISS was 25 (IQR 16–30). The peer-review identified a combination of clinical (85%), systems (51%) and communication (12%) problems that contributed to difficulties in care delivery. In 85% of records, staff actions were identified to contribute to events; with medical task failure the most frequently identified cause (89%). Conclusion: The peer-review of paediatric trauma cases assisted in the identification of contributing factors to clinical incidents in trauma care resulting in 26 recommendations for change. The prioritisation and implementation of these recommendations, alongside a uniform State-wide trauma case review process with consistent criteria (definitions), performance indicators, monitoring and reporting would facilitate improvement in health service delivery to children sustaining severe injury.